ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PELAKSANAN SISTEM PEMBERIAN PELAYANAN KEPERAWATAN PROFESIONAL OLEH PERAWAT PELAKSANA DI RUANG RAWAT INAP RSUD RADEN MATTAHER JAMBI TAHUN 2014 - Indah Mawarti; Fatma Sri Wahyuni; Wawan Wahyudi (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2016)
Abstract Provision of nursing services profesionla system (SP2KP) is a component of the application of professional values ​​in nursing practice, management and provision of nursing care in a hospital ward units and professional development of self. The purpose of this study was to determine the factors associated with the implementation SP2KP by nurses in the hospital inpatient Raden Mattaher Jambi Year 2014 The type of research conducted in this research is quantitative research design using cross sectional analytic study (n = 132 nurses). Test used in this study Chy-Square test. data collection was done by a questionnaire that was tested for validity and reliability. The results of the study analyzes the factors related to the implementation of the system of professional nursing care by nurses diruang Inpatient Hospital Edinburgh Raden Mattaher of the six factors were investigated only one factor of education has a significant association with the implementation SP2KP (p = 0.010). Suggestions researchers to improve the education of nurses ffor this will affect the skill and knowledge of nurses in implementing inpatient space hospitalRSUD Raden Mattaher Jambi Tahun 2014 Keywords : Nurse Executive, Implementation SP2KP, Inpatient space